-3s=-4-s

Simple and best practice solution for -3s=-4-s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3s=-4-s equation:



-3s=-4-s
We move all terms to the left:
-3s-(-4-s)=0
We add all the numbers together, and all the variables
-3s-(-1s-4)=0
We get rid of parentheses
-3s+1s+4=0
We add all the numbers together, and all the variables
-2s+4=0
We move all terms containing s to the left, all other terms to the right
-2s=-4
s=-4/-2
s=+2

See similar equations:

| 9x^2-115x+300=0 | | 4c+10=c | | 11-3v=-19-20+2v | | 3(c−12)=−9 | | 2r+10=4 | | -4d=-5d+12 | | 1/3(18-6x)=10 | | -10+7p-8=-6+9p | | 8k+7=71 | | 4+4n=-9n+4 | | 9b+19=-17+6b | | -48+12x=-24 | | 7u=6u+9 | | -2j+53=20 | | 49=7^(x-5) | | 10-10b=-9+7b+2 | | 12(x+3)=(x+12)+6 | | 12(x+3)=(x+12 | | -7+2c=3c-4 | | 5 | | x+2-6=-3 | | d/9+64=68 | | -2f=-f-4 | | 8+c=-5c-10 | | -9=1/4e-6 | | 1/5(2x+52)=3x | | 3-(1+8n)=23+2n | | 4s=5+5s | | -5n+2=-4n | | 55=7+4p | | y+6y+8y=0 | | 7r+5+8r=-10 |

Equations solver categories